2016
DOI: 10.1111/jfd.12482
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of internalization of white spot syndrome virus by haemocyte subpopulations of penaeid shrimp, Litopenaeus vannamei (Boone), and the outcome for virus and cell

Abstract: Little is known about the innate antiviral defence of shrimp haemocytes. In this context, the haemocytes of penaeid shrimp Litopenaeus vannamei (Boone) were separated by iodixanol density gradient centrifugation into five subpopulations (sub): sub 1 (hyalinocytes), sub 2 and 3 (prohyalinocytes), sub 4 (semigranulocytes) and sub 5 (granulocytes) and exposed to beads, white spot syndrome virus (WSSV) and ultraviolet (UV)-killed WSSV. In a first experiment, the uptake of beads, white spot syndrome virus (WSSV) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Innate immunity is triggered when pathogens are detected by host proteins, such as antimicrobial, coagulation and pattern recognition proteins, which, in turn, activate humoral or cellular effector mechanisms to destroy invading pathogens 22 .…”
Section: Shrimp Immune System and Response To Vaccinesmentioning
confidence: 99%
See 4 more Smart Citations
“…Innate immunity is triggered when pathogens are detected by host proteins, such as antimicrobial, coagulation and pattern recognition proteins, which, in turn, activate humoral or cellular effector mechanisms to destroy invading pathogens 22 .…”
Section: Shrimp Immune System and Response To Vaccinesmentioning
confidence: 99%
“…Recent experimental data from shrimp and other arthropods have shown that invertebrates own an alternative memory type of immune response. This memory-like peculiarity is called resistant priming 22,31 . With this mechanism, shrimps could improve their defenses after initial pathogenic exposure and then generate better protection after subsequent infections with the same or a different pathogen.…”
Section: Shrimp Immune System and Response To Vaccinesmentioning
confidence: 99%
See 3 more Smart Citations